Nonlinear seismic analysis of base-isolated structures - Yang, Guichang (2009)
Base isolation has increasingly become an accepted way for reducing building damage in earthquake-prone areas. One of the most commonly used base-isolation systems comprises laminated high damping rubber bearings positioned at base level of a multi-storied building structure. Base-isolation devices experience large inelastic deformations during a severe earthquake and shift the structural fundamental natural frequency lower and away from the range of frequencies where the earthquake energy is the strongest. The use of laminated high damping rubber bearings can therefore reduce the acceleration response in the superstructure and dissipate energy imparted into the building structure.